Cytomegalovirus infection in pregnant women - threats, diagnosis and treatment - Arkadiusz Grunwald; Kinga Brzuszkiewicz; Katarzyna Nowak; Małgorzata Satora; Jakub Klas; Gracjan Rudziński (Kazimierz Wielki University, 2022)
Cytomegalovirus is one of the most widespread DNA viruses, with 90% of women of childbearing age in Poland infected with it. Infection poses a risk to the mother as well as the fetus, as the virus can cross the placenta and damage the fetus. The purpose of this paper is to review scientific publications from 2017-2022, which describe the course of cytomegalovirus infection in pregnant women, the risks to the mother and fetus associated with the infection, methods of diagnosing the infection in the pregnant woman and the fetus, as well as treatment of cytomegalovirus infection and directions for vaccine research. The most common complications of congenital cytomegalovirus infection include hearing loss, mental developmental delays and miscarriage. The infection can be detected in the pregnant woman by immunological testing, while polymerase chain reaction is used in the fetus and newborn. Early detection of infection in a pregnant woman allows the implementation of treatment which includes ganciclovir, valganciclovir, acyclovir and valacyclovir. A vaccine against cytomegalovirus has not been developed. Particularly important in the prevention of infection is to conduct educational activities regarding the routes of transmission of the virus and the consequences of congenital infection for the fetus. Cytomegalovirus infections among pregnant women. It is important to monitor fetal development and possibly diagnose for congenital CMV infection in case of abnormalities, and the best diagnostic method is polymerase chain reaction testing. For the treatment of congenital CMV infection, acyclovir and valacyclovir are preferred, and therapy should be implemented for specific indications. Attention should be paid to educating women about infections caused by cytomegalovirus.